Risk Factors Associated with the Incident of Hypertension in Pregnant Women in the Gununghalu Community Health Center Working Area - Fajri Kamilatul Muniroh; Dyan Kunthi Nugraheni; Agus Riyanto; Novie E Mauliku; Budiman (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Hypertension or high blood pressure is a condition where blood pressure continuously increases in the blood vessels (WHO, 2018). Gestational hypertension is detrimental to the mother and fetus and carries a risk of developing other cardiovascular diseases in the future. Women with a history of pre-eclampsia or hypertension have a seven to eight times increased risk of morbidity and mortality from coronary heart disease (Subki et al, 2018). Objective: The aim of this research is to determine the relationship between factors that influence the occurrence of hypertension in pregnant women in the Gununghalu Community Health Center working area. Method: This research design used case control with a population of 1,473 and a sample of pregnant women and 63 women with hypertension. Research analysis uses Chi-Square and multivariate analysis using logistic regression analysis. Result: The results of this study show that there is a significant relationship between age and the incidence of hypertension (p=0.0001) OR value of 13,600 (95% CI = 5,782-31,989) which means that pregnant women aged <20 years and >35 years have a risk of hypertension of 13.6 compared to pregnant women aged 20-35 years, there is a significant relationship between gravidity and the incidence of hypertension in pregnant women (p=0.020) OR value obtained of 2,313 (95% CI = 1,132-4,724) which means that pregnant women with primigravida and grande multigravida have a risk of experiencing hypertension of 2.3 compared to pregnant women with multigravida, there is a significant relationship between a history of hypertension and the incidence of hypertension in pregnant women (p=0.000) The OR value obtained was 9.615 (95% CI = 4.238-21.815) which means that people with a history of hypertension in the family have a risk of 9.6 times compared to pregnant women who do not have a history of hypertension in the family, there is a significant relationship between obesity and the incidence of hypertension in pregnant women (p = 0.009) The OR value obtained was 3.949 (95% CI = 1.347-11.574) which means that people who are obese have a risk of suffering from hypertension of 3.9 times compared to pregnant women who are not obese. Conclusion: The conclusion is that all variables in this study have a significant relationship with the incidence of hypertension. It is hoped that all pregnant women will always carry out pregnancy checks with health workers to risks during pregnancy.